Study of the Efficiencies of Algal Species in Removing Pollutants from Sewage Waters - Neelam Verma, Km.; Pathak, Vishal; Yadav, D.C.; Pathak, Prabhat (Asian Journal of Chemistry, 2012)
Three algal species were exploited for the removal of pollutants from sewage water. These algal forms utilized sewage pollutants as nutrients for their growth and development. The algal biomass could be as food and folder since it contained high quality of carbohydrates, fats and proteins. The algal growth indicates the extraction of useful nutrients preset in drain water and thus makes it comparatively pure. The increase in DO indicates the release of oxygen by photosynthetic process. All the remaining parameters, i.e., BOD, COD, different forms of nitrogen, hardness etc. were found decreased. Hence, it can be inferred that algal species may be used as a source for sewage purification and also as a method for the recovery of valuable food materials from the sewage.